Prognostic significance of preoperative neutrophil-to-lymphocyte ratio in surgically resected schwannomas - Takahara, Kento; Tamura, Ryota; Kuranari, Yuki; Karatsu, Kosuke; Akiyama, Takenori; Toda, Masahiro (Frontiers in Oncology, 2023)
Objective: The goal of schwannoma resection is to control the tumor while preserving neurological function. Schwannomas have a variable postoperative growth pattern, therefore preoperative prediction of a schwannoma’s growth pattern is favorable. This study aimed to examine the relationship between preoperative neutrophil-to-lymphocyte ratio (NLR) and postoperative recurrence and retreatment in patients with schwannoma. Methods: We retrospectively examined 124 patients who underwent schwannoma resection in our institution. Associations between preoperative NLR, other patient and tumor characteristics, and tumor recurrence and retreatment were analyzed. Results: Median follow-up was 2569.5 days. Postoperative recurrence occurred in 37 patients. Recurrence that required retreatment occurred in 22. Treatment-free survival (TFS) was significantly shorter in patients with NLR ≥2.21 (P = 0.0010). Multivariate Cox proportional hazards regression showed that NLR and neurofibromatosis type 2 were independent predictors of retreatment (P = 0.0423 and 0.0043, respectively). TFS was significantly shorter in patients with NLR ≥2.21 in the following subgroups: sporadic schwannoma, primary schwannoma, schwannoma ≥30 mm in size, subtotal resection, vestibular schwannoma, and postoperative recurrence. Conclusions: Preoperative NLR ≥2.21 before surgery was significantly associated with retreatment after schwannoma resection. NLR may be a novel predictor of retreatment and assist surgeons in preoperative surgical decision making.